Photoconversion of Alloreactive T Cells in Murine Peyer’s Patches During Acute Graft-Versus-Host Disease: Tracking the Homing Route of Highly Proliferative Cells In Vivo - Jarick, Katja J.; Mokhtari, Zeinab; Scheller, Lukas; Hartweg, Julia; Thusek, Sina; Le, Duc-Dung; Ranecky, Maria; Shaikh, Haroon; Qureischi, Musga; Heinze, Katrin G.; Beilhack, Andreas (Frontiers in Immunology, 2018)
The regulation of immune cell migration throughout the body is essential to warrant immunosurveillance and to maintain immune homeostasis. Marking and tracking of these cells has proven important to study mechanisms of immune cell trafficking and cell interaction in vivo. Photoconversion is a well-suited technique for intravital application because it enables contactless time- and location-specific marking of cells in the tissue without surgically manipulating the microenvironment of the cells in question. However, in dividing cells the converted fluorescent protein may decline quickly. Here, we provide a detailed description of the photoconversion technique and its applicability to tracking highly proliferating T cells from the priming site of T cell activation to peripheral target organs of effector function in a preclinical model. Dendra2+ T cells were photoconverted in the Peyer’s patches during the initiation phase of acute graft-versus-host disease (GvHD) and tracked through the mesenteric lymph nodes and the peripheral blood to the small intestine with flow cytometry and intravital two-photon microscopy. Photoconverted alloreactive T cells preserved the full proliferative capacity, homing and migration of alloreactive T cells in the intestinal lamina propria. We conclusively proved that photoconversion of highly proliferative alloreactive T cells in the Peyer’s patches is an effective tool to study trafficking of alloreactive T cells under physiologic conditions and to GvHD target tissues. This technique can also be applied to the study of immune cell tracking under inflammatory and non-inflammatory conditions.